Anxiety-Depressive Syndrome and Binge-Watching Among Young Adults - Starosta, Jolanta; Izydorczyk, Bernadetta; Wontorczyk, Antoni (Frontiers in Psychology, 2021)
In recent years binge-watching become a highly popular way of spending free time. Even though binge-watching usually is related to entertainment there are concerns about some negative and unhealthy outcomes of excessive form of this behaviour. The study examined the predictive value of anxiety-depressive syndrome in explaining the symptoms of problematic binge-watching and the tendency to adopt a specific motivation to watch series. Research group consist of 645 polish young adults. The State-Trait Anxiety Inventory, Depression Measurement Questionnaire, Viewing Motivation Scale and Questionnaire of Excessive Binge-watching were used in this study. The results of the path analysis show that anxiety-depressive syndrome and motivation to watch TV series are the significant factors in the manifestation of all symptoms of problematic binge-watching. Moreover, there is a significant relation between anxiety-depressive syndrome and motivation to watch TV series, which especially concerns escape motivation and motivation to deal with loneliness. Furthermore, motivation to deal with loneliness, escape motivation and motivation to spend free time have mediating effect on the relationship between anxiety-depressive syndrome and problematic binge-watching. Results of this research show that there could be not only normative binge-watching behaviour but also unhealthy and problematic form of this behaviour.